THE EFFECT OF ADDITIVES ON α-Al2O3 OCCURRENCE KINETICS DURING HEATING OF INDUSTRIAL ALUMINUM HYDROXIDE - Perušić, M.; Obrenović, Z.; Gligorić, M. (Journal of Engineering & Processing Management, 2011)
This paper presents the results of the impact of basic additives in the process of heating (calcinations) of industrial aluminum hydroxide and the formation of the final stable phase α- Al2O3. The influence of additives have been focused on the result of the impact, ie. on the kinetics of crystallization of α-Al2O3, and the comparative analysis of the corresponding activation energies determined for each of the additives used. Based on the experimental results, using a suitable fundamental principles of the Arrhenius equation and suitable statistical tools, it can be concluded about the possible impact of certain quantity additives on the kinetics of the crystallization process, whose results are presented in this paper.